Analysis of the Ukrainian legislation on labour protection adaptation to the European Union acts - S. A. Petrovska; M. V. Petrovskyi (Law and Safety)
The decision of the European Council dated 23 June 2022 to grant Ukraine the status of an EU candidate became a significant incentive for reforms in the country. Reforming labour protection legislation is one of the most urgent tasks for the successful completion of Ukraine’s European integration and for the development of the country’s economy.